Semantika maternje melodije u poeziji Momčila Nastasijevića - Golijanin Elez, Sanja (Slavistična revija, 2015)
The intention in this paper is to investigate into the contex tual historical and poetic positions of interwar (neosymbolic and neoexpressionistic) li terary paths of Momčilo Nastasijević as a continuity of spiritual journey of Serbian poetry in the twentieth century. By applying the poetic and interpretative paradigms, we actualize the tendenc y towards stronger imaginative inclusion of time (history, myth and Christian spirituality/religious spirit of the poetry) in the thick metaphor of "internal pictures", metaphysical and morphological sense of mother melody as a recursive matrix of his poetry.
Keywords: ciklizacija; cyclization; duhovnost; Nastasijević, Momčilo, 1894-1938; poetry; poezija; Serbian literature; Serbian poets; spirituality; srbska književnost; srbski pesniki